A INSTITUIÇÃO BANCÁRIA COMO EXPRESSÃO DO CAPITALISMO AFETIVO: A COMUNICAÇÃO PUBLICITÁRIA DOS BANCOS NO BRASIL - Giannotti, Marcos (2021)
This research analyzes the narratives of financial institutions in Brazil in a critical approach and how they are constituted from the culture of inspiration (CASAQUI, 2017). The research corpus includes both the narratives of traditional banks and new models of banking institu-tions, based on digital platforms. Our work is theoretically based on studies on emotions in the development of capitalism and on the construction of brands through emotions linked to the culture of inspiration, which help to understand the transformation of contemporary ad-vertising communication. The result of this study shows evidence that inspiration, as an effect of meaning produced by discursive strategies linked to emotions, constitutes the rhetorical argument that Brazilian bank brands make use of, calling people to their projects of society and worldviews. An approach that, at the same time, hides the interests related to capital and justifies their actions as financial institutions. In this sense, we identified five perspectives that contribute to the formation of discursive strategies that constitute the inspirational narratives of banks in Brazil. As for the methodology, we used Discourse Analysis (AD), implemented in three stages: the analysis of the communication contract, according to Charaudeau (2006); the identification of emotions as discursive strategies and their effects of meaning, according to the precepts of Ahmed (2015), Ekman (2012, 2021) and Minner (2019); and the semiotic mapping of consumption values, proposed by Semprini (1995).